(untitled) (Journal of the Bangladesh Agricultural University, 2012)
The study was concerned with development of orange flavor emulsion by homogenizing method. Different gum concentration and number of passes were used during emulsion formation. Three different concentration of Gum Arabic (10%, 15% and 20%) and 4, 6 and 8 numbers of passes were used in the experiment. For each concentration of gum 4, 6 and 8 numbers of passes were applied and graphically observed their stability kinetics and microscopic view of particle distribution in emulsion system was observed for each sample through microscope. It was found that at 15% gum concentration and 6 passes was best one and showed most stability than others. DOI: http://dx.doi.org/10.3329/jbau.v9i2.11043 J. Bangladesh Agril. Univ. 9(2): 291296, 2011